Specific Interleukin-1 Inhibitors, Specific Interleukin-6 Inhibitors, and GM-CSF Blockades for COVID-19 (at the Edge of Sepsis): A Systematic Review - Wang, Ying; Zhu, Kun; Dai, Rulin; Li, Rui; Li, Miao; Lv, Xin; Yu, Qian (Frontiers in Pharmacology, 2022)
Introduction: Sepsis is a disease with high mortality, which seriously threatens human health. During the coronavirus disease 2019 (COVID-19) pandemic, some severe and critically ill COVID-19 patients with multiple organ dysfunction developed characteristics typical of sepsis and met the diagnostic criteria for sepsis. Timely detection of cytokine storm and appropriate regulation of inflammatory response may be significant in the prevention and treatment of sepsis. This study evaluated the efficacy and safety of specific interleukin(IL)-1 inhibitors, specific IL-6 inhibitors and GM-CSF blockades in the treatment of COVID-19(at the edge of sepsis) patients through systematic review and meta-analysis. Methodology: A literature search was conducted on Pubmed, EMBASE, Cochrane Library, Clinical Key, Wanfang Database and CNKI were used to search for the proper keywords such as “SARS-CoV-2”, “Corona Virus Disease 2019”, “COVID-19”, “anakinra”, “tocilizumab”, “siltuximab”, “sarilumab”, “mavrilimumab”, “lenzilumab” and the related words for publications published until 22.8.2021. Other available resources were also used to identify relevant articles. The present systematic review was performed based on PRISMA protocol. Results: Based on the inclusions and exclusions criteria, 43 articles were included in the final review. Meta-analysis results showed that, tocilizumab could reduce the mortality of patients with COVID-19(at the edge of sepsis) (RCTs: OR 0.71, 95%CI 0.52-0.97, low-certainty evidence; non-RCTs: RR 0.68, 95%CI 0.55-0.84, very low-certainty evidence), as was anakinra(non-RCTs: RR 0.47, 95%CI 0.34-0.66, very low-certainty evidence). Sarilumab might reduce the mortality of patients with COVID-19(at the edge of sepsis), but there was no statistically significant(OR 0.65, 95%CI 0.36-1.2, low-certainty evidence). For safety outcomes, whether tocilizumab had an impact on serious adverse events (SAEs) was very uncertain (RCTs: OR 0.87, 95%CI 0.38-2.0, low-certainty evidence; non-RCTs 1.18, 95%CI 0.83-1.68, very low-certainty evidence), as was on secondary infections(RCTs: OR 0.71, 95%CI 0.06-8.75, low-certainty evidence; non-RCTs: RR 1.15, 95%CI 0.89-1.49, very low-certainty evidence). Conclusions: This systematic review showed that tocilizumab, sarilumab, anakinra could reduce mortality of people with COVID-19(at the edge of sepsis), and tocilizumab did not significantly affect SAEs and secondary infections. Current evidence of the studies patients treated with siltuximab, mavrilimumab and lenzilumab is insufficient. High-quality studies are needed for establishing stronger quality of evidence.